Language Styles Used by the Main Characters in the Movie Cruella (2021) - Nainggolan, Clara Shinta; Rejeki, Sari; Widodo, Jordy Satria (Universitas Pendidikan Indonesia, 2025)
This study aims to analyze the language styles used by the main characters, Cruella (Estella) and Baroness, in the Cruella movie (2021). The language use of the two main characters is studied because their socioeconomic classes differ, which leads to variances in language styles. Using a qualitative descriptive method, this study analyzes the language styles and communication components that influence the movie Cruella. Martin Joos’ (1967, as cited in Chaer and Agustina, 2010) theory is used to analyze the types of language styles, whilst Hymes’ “SPEAKING” (2013) theory is used to analyze communication component. The data collection technique used is the uninvolved conversation observation (simak bebas cakap) to understand the use of language styles directly. According to the study’s findings, there are 65 language styles: 26 casual style, 22 consultative style, 13 formal style, and 4 intimate style. The use of these language styles is heavily influenced by communication components such as setting, participants, and conversation goals. The results show that casual style dominates the conversation, suggesting that language is more than just a communication tool; it is also a political and psychological domain where identities are at stake.